Rational Clinical Dose Selection of Adeno‐Associated Virus‐Mediated Gene Therapy Based on Allometric Principles. Issue 3 (16th May 2021) - Tang, Fei; Wong, Harvey; Ng, Chee M.
Abstract : One of the challenges in translational medicine is to select first‐in‐human doses of investigational drugs based on findings in preclinical studies. Despite substantial progress in the optimization of recombinant adeno‐associated virus (AAV) vectors of in vivo gene therapy for treating various diseases, there remain significant limitations to the use of preclinical data to guide dose selection in clinical trials. Here we introduce a novel concept of gene efficiency factor (GEF) to describe the efficiency of the gene transfer system and describe and apply the concept of GEF in AAV‐mediated in vivo gene transfer systems. We explore the utility of allometric scaling to translate GEF across species using AAV‐mediated in vivo factor IX (FIX) gene therapy for hemophilia B and to demonstrate the use of GEF in predicting efficacious AAV vector doses in humans. We show for the first time that an allometric relationship exists for GEF of AAV‐mediated in vivo gene therapy. Furthermore, we demonstrate the feasibility of using the allometric relationship of GEF to select efficacious first‐in‐human doses of virus‐mediated in vivo gene therapy. Based on our findings, allometry of GEF can be used to translate biological efficiency from animal studies to clinical studies and provide a rational basis of setting first‐in‐human doses for new virus‐mediated in vivo gene therapy products.